O que pensam alunos de 9ª série do ensino fundamental sobre ciência e cientistas nos desenhos de Jimmy Neutron - Monteiro, Paula Cavalcante (2011)
Over the past five decades of the twentieth century, television became the most powerful source of mass communication. Realizing its importance, several governments and political regimes have been using this media in the propagation of their ideology. This has also been adopted by Science and scientists. This can be evidenced by the number of films, documentaries, diverse programs, specific articles on science broadcast by the family Sunday night programs, and even by cartoons aimed at children. Consciously or not, but endowed with a naive conception and common sense, these programs have been systematically used in order to spread an ideology of science that cultivates the image of a progressist, able to solve all the dilemmas of man, being aseptic and ahistorical. On the other hand, pre-teens and teens are spending long hours in front of the TV, attracted especially by cartoons, some of which portray scientists at work. In our teaching experience, we found that students end up incorporating some naive conceptions of science and that many of them are talking among themselves the option of whether or not they would be a scientist. In this paper we intend to investigate the effect that the animated cartoon "Jimmy Neutron" have on adolescents. Our hypothesis is that their episodes drive the teenagers away from science, causing them to lose interest in becoming scientists. To conduct this work we selected a group of 15 adolescents in the 9th grade. They watched three episodes of the animated cartoon "Jimmy Neutron." After the sessions, they answered a questionnaire and were interviewed about their perceptions and interest in becoming scientists. The testimonies of the students are being analyzed using textual analysis of discourse. After the analysis some misconceptions were identified as that the only function of Science is to invent, Science is incomprehensible for the non-scientist, scientist are unsocial persons and intelligence is innate.